Amitav Ghosh, a critical companion - Khair, Tabish (Delhi : Permanent Black : Distributed by Orient Longman, 2003)
Contributed articles on the life and works of Amitav Ghosh, Indian English author.
"Travelling in the West": the writing of Amitav Ghosh / Robert Dixon -- Historicizing scientific reason in Amitav Ghosh's the circle of reason / Claire Chambers -- "A choice of histories": Ghosh vs. Hegel in in an antique land / Padmini Mongia -- "The burthen of the mystery": imagination and difference in the shadow lines / Jon Mee -- Des kothay? Amitav Ghosh tells old wives tales / Anjali Gera -- The discoverer discovered: Amitav Ghosh's the Calcutta chromosome: the question of subaltern agency / Tabish Khair -- The road from Mandalay: reflections on Amitav Ghosh's the glass palace / Rukmini Bhaya Nair.
Includes bibliographical references (p. [175]-183).
Keywords: Ghosh, Amitav -- Criticism and interpretation